Poverty and livelihood impacts of community based fisheries management in Bangladesh - Md. Nurul Islam, Gazi; Tai, Shzee Yew; Viswanathan, K. Kuperan (Elsevier, 2014)
We examine the impact of the Community Based Fisheries Management (CBFM) on welfare of fishing households in Bangladesh. Our analyses demonstrate how the various types of livelihood assets contribute to household income of fishers in different types of water body areas such as closed beels (deeper depressions in the floodplain), open beels (lake), floodplain beels and rivers. Data for the study were obtained from two questionnaire-based field surveys conducted by the Bangladesh CBFM project office: a baseline study carried out in 2002 and an impact study in mid-2006. A total of 1 994 households were randomly selected from 34 (51%) CBFM project water bodies in Bangladesh. Our study shows that fisher's income has significantly increased in floodplain beels (FPB), open beels (OB), and rivers. Fishers' income from fishing has been significantly reduced in closed beels (CB) due to excessive lease fees and stocking costs for aquaculture. The regression results indicate that natural, physical, and financial assets have significantly contributed to income of the fisher households in open beels, rivers, and floodplain beels. The CBFM organized fishers have changed their attitudes, improved trust, and resolved conflicts in open beels. Results of the study suggest that natural, physical, and financial assets play very significant roles in poverty reduction in CBFM areas in Bangladesh. There is a need to give priority to investment in social capital and financial credit for reducing poverty of fishers of Bangladesh.